Assessment of the diversity of the family Sillaginidae in the Indian Ocean with emphasis on the taxonomic identity of Sillago sihama - Saha, Shilpi; Bogorodsky, Sergey V.; Baki, Mohammad Abdul; Gao, Tianxiang; Mckay, Roland J.; Alpermann, Tilman J.; Song, Na (Zootaxa, 2024)
The present study contributes to the taxonomy of the family Sillaginidae, with comments on the distribution of its species in the Indian Ocean and an emphasis on the taxonomy and distribution of Sillago sihama. Thirty described and putative species with Indian Ocean distribution are listed, and a distribution range for each species is provided based on published data and results from the present study. A comprehensive phylogenetic analysis of the barcoding portion of the mitochondrial COI gene is provided together with three approaches for molecular species delimitation, which includes 44 to 47 genetic lineages (depending on the species delimitation approach used) in the family Sillaginidae, 33 of them applying to described species and also 8 putative species, formerly misidentified as S. sihama. Inclusion of specimens from South Africa, Iran, Pakistan, India, Bangladesh and the southern Red Sea (type locality) reveals one genetic lineage representing the true Sillago sihama. Distribution of the species is confined to the Red Sea and the Indian Ocean, and other records under the name S. sihama are based on misidentifications. Several undescribed species identified as S. sihama are distributed in the Indo-West Pacific region and closely resemble S. sihama, but are not identical with this species and can be identified as members of different evolutionary lineages. Two species, S. sihama and S. soringa, reported from Bangladesh, represent the easternmost record of both species. These two species are described in detail, including swimbladder morphology. The study also shows that specimens from India identified as Sillago ingenuua McKay, 1985 are nested within a lineage previously referred to as S. ingenuua A, but are different from the lineage S. ingenuua B, representing a confirmed record of the clade S. ingenuua in the northern Indian Ocean. Comments on misidentifications of S. sihama from the Indian Ocean and western Pacific are provided. Furthermore, we propose that Sillago erythraea should be resurrected from its synonymy with S. sihama. As Sillago suezensis is identical with the former species, it becomes a junior synonym of S. erythraea.